IMPLEMENTASI KEBIJAKAN E-PROCUREMENT PENGADAAN BARANG DAN JASA PADA LEMBAGA LAYANAN PENGADAAN SECARA ELEKTRONIK (LPSE) PROVINSI SULAWESI TENGAH - Putri, Zarina Dwi (Katalogis, 2016)
This study aims to determine the Implementation of Goods and Services E-Procurement at the Electronic Procurement Service (Layanan Pengadaan Secara Elektronik - LPSE) of Central Sulawesi Province. The type of this study is qualitative descriptive research. Informants in this study amounted to consisting ofÂ  Head of the Electronic Procurement Service (Layanan Pengadaan Secara Elektronik - LPSE) of Central Sulawesi Province, Secretary of the Electronic Procurement Service (Layanan Pengadaan Secara Elektronik - LPSE) of Central Sulawesi Province, andÂ  Division Coordinators at the Electronic Procurement Service (Layanan Pengadaan Secara Elektronik - LPSE) of Central Sulawesi Province. The theory used in this study was the implementation theory of Grindle which has two major variables , namely the content of the policy and the policy context. The data collection was done through observations, interviews and documentations. The data analysis technique used in this study comprised data reduction, data display, conclusion, and verification. Based on the results of this research and the data processing, it can be concluded that the implementation of Goods and Services E-Procurement at the Electronic Procurement Service (Layanan Pengadaan Secara Elektronik - LPSE) of Central Sulawesi Province had been going well, it is just some obstacles in the process, such as lack of employee discipline, lack of facility resources, and the Electronic Procurement Service (Layanan Pengadaan Secara Elektronik - LPSE) of Central Sulawesi Province which was still an ad-hoc to the Development and Natural Resources Administration Bureau of Central Sulawesi Regional Secretariat.